Rollover risk in commercial paper markets and firms' debt maturity choice - Felix Thierfelder (Deutsche Bundesbank, 2008)
By using short-term direct finance firms of the highest credit quality expose themselves to rollover risk in the public debt markets. Firms insure themselves against this risk by securing backup lines of credit from banks that they may use should market liquidity dry up. In a first step, this paper explains why high quality firms introduce a maturity mismatch into their balance sheets and do not simply use long-term direct finance. It also highlights why banks may be willing to roll over a firm's debt while direct investors may not. In a second step, I extend the model to allow for different levels of firm's publicly observable credit quality. Under plausible assumptions about the cost of bank borrowing the model generates a maturity structure choice broadly consistent with observed financing patterns: Low quality firms issue short-term direct debt, medium quality firms issue long-term direct debt, and high quality firms use short-term direct debt in normal times and bank debt in adverse times. The paper suggests that better publicly available information about firm quality and the moderation of the business cycle over the past decade help to explain the decrease in nonfinancial commercial paper outstanding since the beginning of the decade. – – Kapitalmarktfähige Unternehmen können sich nur dann durch die Ausgabe von kurzfristigen Geldmarktpapieren (Commercial Paper - CP) refinanzieren, wenn sie eine vernachlässigbare Ausfallwahrscheinlichkeit aufweisen. Gleichwohl ist es diesen Firmen bisweilen nicht moglich, eine Anschlussfinanzierung vorzunehmen. In solchen Situationen können CP-Emittenten auf Kreditlinien ausweichen, sofern sie diese zuvor mit Banken vereinbart haben und sich ihre Kreditqualität bei Inanspruchnahme der Kreditlinie nicht verschlechtert hat. In dem vorliegenden Papier werden zunächst zwei Fragenkomplexe näher untersucht. Erstens, warum bekommen Firmen von höchster Kreditqualität zu bestimmten Zeiten keinen Kredit, obwohl ihre tatsächliche Ausfallwahrscheinlichkeit nahe null liegt? Zweitens, warum wählen diese Firmen eine Finanzierungsform, bei der sie sich in guten Zeiten über die Ausgabe von Geldmarktpapieren finanzieren und in schlechten Zeiten einen Bankkredit in Anspruch nehmen? Warum nehmen sie eine Inkongruenz der Laufzeiten zwischen Aktiv- und Passivseite in Kauf, anstatt lang laufende Anleihen zu emittieren und sich somit keinem Refinanzierungsrisiko auszusetzen?
Keywords: G32; G21; D82; 330; Rollover risk; Liquidity; Asymmetric Information; Debt maturity; Finanzierungstheorie; Kredit; Laufzeit; Commercial Paper; Kreditrisiko; Theorie